Lalu dan Kini: Identifikasi Tatanan Kawasan Heritage di Kawasan Talang Semut Kota Palembang - Listen Prima; Almira Ulfa; Indah Nurlia Afiyah; Chiquita Mutiara; Melina Alifah Putri (Archvisual: Jurnal Arsitektur dan Perencanaan, 2022)
Heritage has been understood as the history, traditions, and values of a nation or country over the years and as well as an important value of their character. Talang Semut area is one of the heritage areas of Palembang City that needs to be taken into account by the government in environmental analysis and its historical impact, especially in terms of its heritage authenticity. In this research, a qualitative method in the form of surveys is applied to collect data, then processed and mapped through the ArcGIS application. The results of the study are described using descriptive methods through various surveys data and related journal references. The result of the research indicates that the heritage area of Talang Semut has a strong relation of its development. This research is expected to be a reference for information to strengthen the heritage characteristics of Palembang City and also as a reference in the development of other heritage areas in Palembang City.